Metabolic Implications of Oxidative Stress and Inflammatory Process in SARS-CoV-2 Pathogenesis: Therapeutic Potential of Natural Antioxidants - Forcados, Gilead Ebiegberi; Muhammad, Aliyu; Oladipo, Olusola Olalekan (Front. Cell. Infect. Microbio, 2021)
COVID-19 is a zoonotic disease with devastating economic and public health impacts globally. Being a novel disease, current research is focused on a clearer understanding of the mechanisms involved in its pathogenesis and viable therapeutic strategies. Oxidative stress and inflammation are intertwined processes that play roles in disease progression and response to therapy via interference with multiple signaling pathways. The redox status of a host cell is an important factor in viral entry due to the unique conditions required for the conformational changes that ensure the binding and entry of a virus into the host cell. Upon entry into the airways, viral replication occurs and the innate immune system responds by activating macrophage and dendritic cells which contribute to inflammation. This review examines available literature and proposes mechanisms by which oxidative stress and inflammation could contribute to COVID-19 pathogenesis. Further, certain antioxidants currently undergoing some form of trial in COVID-19 patients and the corresponding required research gaps are highlighted to show how targeting oxidative stress and inflammation could ameliorate COVID-19 severity
Keywords: COVID-19; oxidative stress; inflammation; therapeutics; antioxidants; Ahmadu Bello University; ACENTDFB